Synthesis and thermal behavior of two Sr(II) compounds derived from isomeric 5-(n-pyridyl)tetrazole-2-isopropionic acid (n = 2, 3). Issue 8 (17th April 2020) - Hao, Xinyu; Li, Yan; Liu, Xiaoyi; Ren, Jing'Ao; Shi, Conghao; Liu, Yuanhui; Wang, Zhikang; Du, Zixiang; Li, Qiaoyun; Yang, Gaowen
Abstract: Isomers play a crucial role in the formation of coordination architectures. Herein we report two Sr(II) coordination compounds, mononuclear [Sr(2-pytzipa)2 (H2 O)4 ] (1 ) and 1D [Sr(3-pytzipa)2 (H2 O)2 ] n (2 ) derived from two isomers, 5-( n -pyridyl)tetrazole-2-isopropionic acid (Hn-pytzipa, n  = 2, 3). Furthermore, differential scanning calorimetry and thermogravimetric-differential thermogravimetric analyses were applied to evaluate the thermal decomposition behavior of such compounds. The relevant thermodynamic parameters (Δ H, Δ S, and Δ G ) of the decomposition process of 1 and 2 were calculated as well. Graphical Abstract: